2019
DOI: 10.1371/journal.pbio.3000283
|View full text |Cite
|
Sign up to set email alerts
|

Neurocomputational mechanisms at play when weighing concerns for extrinsic rewards, moral values, and social image

Abstract: Humans not only value extrinsic monetary rewards but also their own morality and their image in the eyes of others. Yet violating moral norms is frequent, especially when people know that they are not under scrutiny. When moral values and monetary payoffs are at odds, how does the brain weigh the benefits and costs of moral and monetary payoffs? Here, using a neurocomputational model of decision value (DV) and functional (f)MRI, we investigated whether different brain systems are engaged when deciding whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 95 publications
3
42
0
2
Order By: Relevance
“…This design allows us to investigate whether testosterone is involved in guiding prosocial vs. selfish decisions induced by the presence of an audience when participants face a moral dilemma. Because weighing monetary costs against compliance with one's moral values (Qu et al, 2019) and perceiving one's good reputation (Izuma et al, 2008(Izuma et al, , 2010 have been reported to result in striatal activity, we hypothesize a positive correlation between testosterone levels and striatal activation while making prosocial decisions in reaction to the presence of an audience.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…This design allows us to investigate whether testosterone is involved in guiding prosocial vs. selfish decisions induced by the presence of an audience when participants face a moral dilemma. Because weighing monetary costs against compliance with one's moral values (Qu et al, 2019) and perceiving one's good reputation (Izuma et al, 2008(Izuma et al, , 2010 have been reported to result in striatal activity, we hypothesize a positive correlation between testosterone levels and striatal activation while making prosocial decisions in reaction to the presence of an audience.…”
Section: Introductionmentioning
confidence: 94%
“…We summarize in this section the experimental design, all the details being developed in Qu et al (2019). Twenty-four healthy male participants, aged 22.47±2.62 years, with no history of neurological or psychiatric illness participated in the fMRI experiment.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent study exploring how the brain solves the conflict between moral value and monetary value reported that the insula and lateral prefrontal cortex engage in weighing monetary benefits and moral costs while the putamen engages in weighing monetary costs against compliance with one’s moral values. Thus, the authors suggested that reward-related regions, especially the striatum, are involved in processing both moral and economic values, and that these representations interact with each other (Qu et al, 2019). These findings indicate that reward circuitry might play a significant role in resolving the conflict between morality and economic interests.…”
Section: Introductionmentioning
confidence: 99%